Profesionalisme Kepala Paud Dalam Pengembangan Mutu Pembelajaran Berbasis Islam - Tati Khafidotur Rofingah; Syamsul Bahri Tanrere; Ahmad Zain Sarnoto (Departement of Mathematics Education, 2024)
The conclusion of this research is that a PAUD Head who is professional and optimal in carrying out his duties can mobilize PAUD educators, PAUD students, student guardians, and other PAUD stakeholders optimally so that the vision and mission of PAUD institutions can be realized well and produce quality education and learning quality. maximum. This research uses qualitative research methods, with the type of research carried out by researchers being library research, namely the study of documents or texts. If seen from the nature of the research, this research is descriptive research. The results of this research show that: First, the concept of PAUD heads in improving the development of the quality of Islamic-based learning in Early Childhood Education (PAUD) includes: a. PAUD heads upgrading themselves to learn and collaborating with other institutions, b. PAUD heads motivating PAUD educators to be more creative and innovative in providing learning in class to get rewards, c. Before entering class or Teaching and Learning Activities (KBM), children are given the habit of reading Asmaul Husna, daily prayers or short suras, d. religious extracurriculars, providing counseling guidance, making students more effective, and e. Educate children to learn to save with sharia savings. Second, the PAUD head's professional leadership style model in developing the quality of Islamic-based learning is the PAUD head's visionary leadership style. Because, PAUD heads who practice a visionary leadership style become futuristic, democratic individuals, and lead their PAUD institutions with an optimistic attitude. This optimism is shown by his attitude of always learning and encouraging PAUD educators and PAUD education staff to always learn too.